In situ neutron diffraction analysis of stress-free d-spacing during solution heat treatment of modified 319 Al alloy engine blocks. (January 2015) - Lombardi, A.; Sediako, D.; Ravindran, C.; MacKay, R.
<x content-type="archive" xml:space="preserve">Abstract</x> Aluminium alloy engine blocks have successfully replaced ferrous materials in order to maximise weight savings and improve vehicle fuel efficiency. However, the development of an optimal heat treatment process is required to improve engine block casting integrity and prevent potential problems such as in-service cylinder distortion. Optimisation of heat treatment parameters requires an in-depth study to determine how residual stresses are relieved with time during solution heat treatment. In order to perform this analysis, however, in situ neutron diffraction must first be carried out on stress-free samples of the same composition and processing history as the engine blocks to account for factors such as thermal expansion and changes in lattice parameter due to dissolution of secondary phases. The results from this study suggest that thermal expansion caused the largest change in d0 spacing, while prolonged exposure at the solutionising temperature resulted in relatively small changes in {311} and {331} d0 spacing due to phase dissolution. Les blocs-moteurs en alliage d'aluminium ont remplacé avec succès les matériaux ferreux afin de maximiser l'économie de poids et d'améliorer le rendement énergétique du véhicule. Cependant, le développement d'un procédé optimal de traitement thermique est requis afin d'améliorer l'intégrité du moulage du bloc-moteur et d'empêcher des problèmes potentiels comme la déformation du cylindre durant l'usage. L'optimisation des paramètres de traitement thermique requiert une étude en profondeur afin de déterminer comment les contraintes résiduelles sont relâchées en fonction du temps durant le traitement thermique de mise en solution. Toutefois, avant d'effectuer cette analyse, on doit d'abord effectuer la diffraction des neutrons in situ d'échantillons sans contrainte de même composition et de même histoire de traitement que les blocs-moteurs pour tenir compte de facteurs comme l'expansion thermique et les changements de paramètre de réseau dus à la dissolution de phases secondaires. Les résultats de cette étude suggèrent que l'expansion thermique produit le plus grand changement de l'espacement d0, alors que l'exposition prolongée à la température de mise en solution produisait des changements relativement petits de l'espacement d0 {311} et {331} à cause de la dissolution de phase.